Promoting Foods to Indian Children through Product Packaging - Soni Pavleen (Journal of Competitiveness, 2013)
Packaging serves as an important mass communication tool to market foods in stores. Packaging elements such as bright colours, spokes/cartoon characters, cartoonish scripts/crayoned fonts, discounts and premiums are used to attract children and influence their consumption behaviour. Use of these practices is widely researched in developed countries. However, these practices are witnessed to be used in developing countries like India as well. So, it is important to objectively assess the nature and extent of promotions used on food packages in Indian settings. The present study is based on content analysis of food packages. It is found that Indian children are exposed to a wide range of food promotions through food packaging. The extent of promotions used in India is very similar to the practices followed in other countries. Implications of these practices are finally discussed in the paper.